2021
DOI: 10.3389/fped.2021.615724
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immune Response and Cytokine Production in CD70 Deficiency

Abstract: Collective clinical and immunologic findings of defects in the CD27–CD70 axis indicate a primary immunodeficiency associated with terminal B-cell development defect and immune dysregulation leading to autoimmunity, uncontrolled viral infection, and lymphoma. Since the molecular mechanism underlying this entity of primary immunodeficiency has been recently described, more insight regarding the function and profile of immunity is required. Therefore, this study aimed to investigate stimulated antibody production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…This indicates that silencing of CD70 may be a viable option for overcoming CD70CAR-T fratricide, improving viability of CD70CAR-T cells. However, as recent investigation noted the impact of CD70 deficiency on the function of CD8 T cells, 100 the possibility of selectively expanding CD4+ CAR-T cells, already shown to be more effective against GBM, 101 would be even more relevant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that silencing of CD70 may be a viable option for overcoming CD70CAR-T fratricide, improving viability of CD70CAR-T cells. However, as recent investigation noted the impact of CD70 deficiency on the function of CD8 T cells, 100 the possibility of selectively expanding CD4+ CAR-T cells, already shown to be more effective against GBM, 101 would be even more relevant.…”
Section: Resultsmentioning
confidence: 99%
“…Limiting dilution analysis GBM cells (CD70+/CD70-or Control/CD70 Knockout cells) were plated at varying densities (1,3,5,10,15,25,50,75,100,125,150, 200 cells/well) were flow-sorted onto a low-binding 96-well plate. Cells were cultured in 200 µL of media and incubated for 4 days at 37°C and 5% CO 2 .…”
Section: Glycocapture Proteomicsmentioning
confidence: 99%
“… 60 Defects in the CD27–CD70 axis indicate an immunodeficiency associated with terminal B-cell development defect and immune dysregulation leading to autoimmunity, uncontrolled viral infection, and lymphomas. 61 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the present study revealed that CD27 and CD70 gene expression was significantly lower in the non-lesional areas compared to HCs. Interestingly, Abolhassani [ 23 ] reported two family members with genetic abnormalities in the CD70- CD27 signaling cascade associated with clinical features of AA, Behcet's disease, recurrent viral pneumonia, central nervous system infection, and Hodgkin lymphoma induced by Epstein–Barr virus. The patients' clinical and immunologic data revealed an abnormality in B-cell differentiation, impaired functional activity of effector T cells, and decreased antibody production, which increased vulnerability to recurrent viral illness.…”
Section: Discussionmentioning
confidence: 99%